RESPONSE OF GREENHOUSE GROWN TOMATO (Lycopersicum esculentum Mill ) TO SOILLESS MEDIA AND VARYING IRRIGATION SYSTEMS (2014)
Soilless farming of vegetables in greenhouse has become a profitable venture in some parts of the world. A high degree of competence in engineering skills, irrigation techniques and cost reduction is required for its successful operation. In Nigeria, the potential of soilless farming in greenhouses has not received adequate attention. The use of soilless media and appropriate irrigation system to produce marketable tomato in a greenhouse were investigated. Roma VF variety of tomato was planted in a greenhouse in Owo, Ondo state in six soilless media: sand, sawdust, Coconut Fiber (CF), Sand/Sawdust (1:1) (SS), Sawdust/CF (1:1) (SCF) and CF/Sand (1:1) (CFS). The control was tomato grown directly on a clayey loam soil adjacent to the greenhouse. Drip and micro sprinkler irrigation units were designed, constructed and calibrated. These were used to fertigate the crop with a pre-mix NPK 20:20:20 liquid fertilizer. The experiment was a 2 x 6 factorial combination with three replicates using completely radomised design. Water Use Efficiencies (WUE) of tomato were calculated while crop coefficients (Kc) and Potential Evapotranspiration (ETp) of tomato were estimated using combination of data obtained from the greenhouse and that of a nearby weather station. Yield and percentage of marketable fruits of tomato were determined at maturation. The experiment was repeated for two growing cycles. Data were analysed using ANOVA at p = 0.05. Cost benefit analyses of using drip versus micro sprinkler irrigation system and the use of soilless media versus soil were evaluated. Mean temperature and relative humidity inside and outside the greenhouse were 31±2 oC and 79±3 % and 27±2 oC and 74±3 %, respectively. The uniformity coefficient obtained for the sprinkler unit was 91 %, while the emission uniformity of the drip was 95 %. Total amount of water used by sprinkler was three times the amount used by the drip irrigation. The WUE of tomato varied from 5.4 to 6.8 g/l under sprinkler and 16.7 to 24.4 g/l under drip irrigation. The mean of Kc values varied between 0.44 and 0.92 and the ETp values ranged between 93.3 and 158.9 mm. The CFS and CF produced the highest number of fruit yield of 5.9 and 5.6 kg/plant, respectively, while the control produced least value of fruit yield (2.1 kg/plant). There was a significant difference between yield of tomato under sprinkler and drip irrigation systems. The percentage of marketable fruits was 92, 85, 82, 80, 79, 78 and 60 for CFS, sand, CF, SCF, SS, sawdust and control, respectively. The benefit-cost ratio of drip irrigation versus micro sprinkler irrigation was 2:1, while that of soilless media versus soil was 6: 1. Soilless planting produced tomato of higher yield and there was marked increase in production for the two growing cycles. Mixture of coconut fiber and sand (1:1) and drip irrigation system is recommended for the practice of greenhouse-grown tomato in the study area.